How older people living with HIV narrate their quality of life: Tensions with quantitative approaches to quality-of-life research - Dana Rosenfeld; Jane Anderson; Jose Catalan; Valerie Delpech; Damien Ridge (Elsevier, 2021)
This article draws on life-history interviews with older (aged 50+) people living with HIV in England to uncover the interpretive practices in which they engaged as they evaluated their own quality of life (QoL). Our paper highlights the distinctive insights that biographical and narrative approaches can bring to QoL research. While accounts of subjectively 'poor' QoL were relatively straightforward and unequivocally phrased, accounts of subjectively 'good' and 'OK' QoL were produced using complex interpretive and evaluative practices. These practices involved biographical reflection and contextualization, with participants weighing up and comparing their current lives' 'pros' and 'cons', their own lives with the lives of others, and their present lives with lives they had imagined having at the time of interview. Thus, 'good' and 'OK' QoL were constructed using practical, relational, and interpretive work - features of QoL analytically unavailable in quantitative data gathered through standardised measures (including our own survey data collected from these same participants). Our findings underscore the uneasy fit between QoL's quantitative measurement and its subjective understandings and evaluations, on the one hand, and the interpretive work that goes into achieving these understandings and evaluations, on the other.